Socjalizacja poznawcza jako (d)efekt kształcenia szkolnego (na tle rozważań nad kulturowym kontekstem konstruowania struktur poznawczych człowieka) - Astrid Męczkowska-Christiansen (Problemy Wczesnej Edukacji)
Issues taken in the presented article refer to the relationship bet ween culture, the development of human cognitive structures, and school education. Starting from the theses presented within the discourse of contemporary cultural psychology I analyse the role of culture in the development of human cognitive abilities, where further references to the concept of cognitive socialization are made. Finally I make an attempt to point out the principles of effective cognitive socialization in the area of formal education which provides the basis for a sketchy evaluation of the impact of contemporary education on the effects of the cognitive socialization process.